Study of the Quality of Work Life and the Collateral Effects of COVID-19 on Workers of Universities in the State of Sonora, Mexico (2022)
The objective of this research work is to know the level of quality of working life and the collateral effects of COVID-19 on workers of universities in the state of Sonora, with a mixed methodological design, analyzing three dimensions within the instrument: quality of working life, organizational management and organizational performance, with the support of 419 workers who participated from various universities. The assessments of the dimensions were obtained as results, which determine that the quality of life variable is 3.71, which is favorable, while the level of collateral affectation by the pandemic is 3.5, which is not favorable, due to the fact that in the new remote modality spaces are not promoted to interact with the staff in activities other than those of daily work, there are no resources, equipment, tools or materials to carry out the activities properly; so, faced with this situation,  collaborators have been forced to adapt to new ways of working with the challenges that this entails. JEL Codes: 65, I3 y 51 Received: 15/09/2022.  Accepted: 13/10/2022.  Published: 01/12/2022.